Onions and Other Vegetable Alliums, (2nd Edition) - Brewster, James L (CABI, 2014)
A number of people, including lecturers, researchers and seed company staff, have told me that they found the first edition of this book useful. This is the best reward for writing such a book. A lot of new allium science has been published since the first edition and progress has been rapid, particularly in the fields of genetics, plant breeding and plant pathology, where the techniques of molecular biology have had great impact. So, an attempt at an update was clearly worthwhile. Shortly before writing the first edition I had co-edited the multi-author Onions and Allied Crops with Haim Rabinowitch, so up to date reviews by experts in the relevant science were to hand and familiar to me. For this edition, I have had to resort more to the original research literature, although the reviews by contributors to Rabinowitch and Currah’s (2002) Allium Crop Science: Recent Advances were key sources for many topics. A book of this breadth cannot attempt to be an exhaustive review of the research literature and, inevitably, in choosing what research to mention, there is some bias to what I am familiar with, notably towards work from Wellesbourne, from the UK and what is published in English. I apologize to those who have done interesting work which is not mentioned but, nevertheless, I hope the book gives a reasonable overview of the current scientific understanding about the vegetable alliums. I hope this second edition will help to raise and maintain awareness of the huge and continuing achievement of allium scientists in discovering so much fascinating and useful information about these crops. These researchers are the real heroes and heroines behind this book. I hope I have not misrepresented their work by error, omission or misplaced emphasis